Arabization of Sports Terms on the Emarat Al-Yaoum Website - Abdul Jabbar Siddiq Syah; Mugy Nugraha (Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
Sports are more than just games; they have become a platform for building bilateral relationships. Many sports have gained international prominence and entered the Arab world, such as the Qatar World Cup and others, leading to the absorption of foreign sports terminology into the Arabic language. This study aims to identify the Arabization (ta'rib) rules used by the news website